Effects of shading and simulated grazing on carbon sequestration in a tropical seagrass meadow. (12th March 2016) - Dahl, Martin; Deyanova, Diana; Lyimo, Liberatus D.; Näslund, Johan; Samuelsson, Göran S.; Mtolera, Matern S. P.; Björk, Mats; Gullström, Martin
Summary: There is an ongoing world‐wide decline of seagrass ecosystems, one of the world's most efficient carbon sink habitats. In spite of this, there is a clear lack of studies experimentally testing the effects of anthropogenic disturbances on carbon sequestration of seagrass systems. We assessed the effects of two disturbances of global concern on the carbon sink function in a five‐month in situ experiment within a tropical seagrass ( Thalassia hemprichii ) meadow by testing the impacts of shading and simulated grazing at two levels of intensity using shading cloths and clipping of shoot tissue. We measured the effects of these disturbances on the carbon sequestration process by assessing the net community production (NCP), carbon and nitrogen content in tissue biomass, and organic matter and THAA (total hydrolysable amino acids) in the sediment down to 40 cm depth. Treatments of high‐intensity shading and high‐intensity clipping were similarly impacted and showed a significantly lower NCP and carbon content in the below‐ground biomass compared to the seagrass control. No significant effects were seen in organic carbon, total nitrogen, C:N ratio and THAA in the sediment for the seagrass treatments. However, both clipping treatments showed different depth profiles of carbon and THAA compared to the seagrass control, with lower organic carbon and THAA content in the surface sediment. This can be explained by the clipping of shoot tissue causing a less efficient trapping of allochthonous carbon and reduced input of shredded seagrass leaves to the detritus sediment layer. In the clipping plots, erosion of the surface sediment occurred, which was also most likely caused by the removal of above‐ground plant biomass. Synthesis . Our findings show that during the course of this experiment, there were no impacts on the sedimentary carbon while the high‐intensity disturbances caused a clear depletion of carbon biomass and reduced the seagrass meadow's capacity to sequester carbon. From a long‐term perspective, the observed effect on the carbon biomass pool in the high‐intensity treatments and the sediment erosion in the clipping plots may lead to loss in sedimentary carbon. Abstract : In an in‐situ experiment, we assessed the effects of two disturbances of global concern on carbon sequestration in a tropical seagrass meadow. While no impacts were detected on the long‐term storage of sedimentary carbon, high‐intensity disturbances showed a lower NCP and a clear depletion of carbon biomass, leading to a reduction in the capacity to sequester carbon.